2018
DOI: 10.1177/0956462418799803
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for gout in HIV-positive adults: A case–control study

Abstract: Gout is the most common inflammatory arthritis worldwide. Its principal risk factor is hyperuricaemia. While gout has been described in HIV patients and numerous more outdated anti-retroviral therapies (ARTs) have been implicated, there have been few recent studies. Our case–control study investigated the prevalence of and risk factors for gout in an established HIV cohort. Cases were identified from database searches using key search terms, with two age- and gender-matched controls. These were compared for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…38 However, new studies reveal that gout in HIV-infected people is not associated with HAART and that nonnucleoside reverse transcriptase inhibitors may even protect against gout (odds ratio, 0.3; 95% confidence interval, 0.1-0.9). 38 Most gout cases in HIV-infected patients are linked with traditional risk factors including hypertension, male sex, and African American race.…”
Section: Crystalline Arthritismentioning
confidence: 99%
See 2 more Smart Citations
“…38 However, new studies reveal that gout in HIV-infected people is not associated with HAART and that nonnucleoside reverse transcriptase inhibitors may even protect against gout (odds ratio, 0.3; 95% confidence interval, 0.1-0.9). 38 Most gout cases in HIV-infected patients are linked with traditional risk factors including hypertension, male sex, and African American race.…”
Section: Crystalline Arthritismentioning
confidence: 99%
“…Gout is the most common inflammatory arthritis across the world. Prior literature suggested a strong association between HIV-infected people and gout thought to be due to early antiretroviral therapies linked to lipodystrophy and dyslipidemia 38 . However, new studies reveal that gout in HIV-infected people is not associated with HAART and that nonnucleoside reverse transcriptase inhibitors may even protect against gout (odds ratio, 0.3; 95% confidence interval, 0.1–0.9) 38 .…”
Section: Crystalline Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperuricemia was increasingly seen among people living with HIV on ART than in the general population, which indicates people living with HIV are at greater risk of cardiovascular disease (CVD) than HIV-negative people, which means attention must be given to these people to prevent CVD ( 20 ). An increased risk of having hyperuricemia was seen among treatment-naive compared to treatment experienced people living with HIV ( 21 , 22 ). It is observed that hyperuricemia was also detected in HIV patients taking HAART ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Развитие подагры также не является редкостью, поскольку не только длительно персистирующая ВИЧ-инфекция, но и развивающиеся при СПИД онкологические заболевания, а также проведе-ние АРВТ нередко способствуют значительному повышению уровня мочевой кислоты (МК) [9]. Напротив, применение ненуклеозидных ингибиторов обратной транскриптазы для лечения ВИЧ снижает риск гиперурикемии [10].…”
unclassified